Evaluation of Two Heat Sum Calculation Methods in Maize Production - Dorka, Dénes (Acta Agraria Debreceniensis, 2005)
Maize production is of primary importance in Hungary, especially considering that its cultivation takes up one of the greatest ratios of land used for agricultural production. As a result, the number of farms where maize is not cultivated for either food production or foraging purposes is insignificant. For this reason, establishing economic production is of decisive importance when it comes to determining the efficiency of farms. Profitable maize production depends on a number of conditions, including the professional suitability of farmers, while some aspects of production are independent from these. Heat-sum calculations form a transition from this aspect, since temperatures ocuring during the growing season cannot be influenced by man. However, the method of calculation and evaluation and thus the tool to improve production is in the hands of the farmer. This scientific paper aims to give a general description of heat-sum calculation methods.